An Evaluation Study of Structural Analysis and Design Software - Samat, Muhammad Fitri; Md Noh, Mohammad Soffi (Recent Trends in Civil Engineering and Built Environment, 2024)
Abstract: Analysis and design structure without computer use is unimaginable and unavoidable in this era compared to the previous generation, especially when it comes to complex structures, which also involve complex geometry. Because of the rapid technology has involved, several software has been developed throughout the year, which has its unique feature on each software. However, the comparative study between different structure design software in Malaysia was not well established. Therefore, this study aim to investigates the differential between analysis and design software commercially available in the Malaysian market. A four-story reinforced concrete building was chosen as a case study throughout this project using three different Softwares, namely as ESTEEM, Tekla, and Robot Structure Analysis. The result obtained from manual calculation and software is dissimilar even though not a lot compared to manual calculation. The time-consuming design and analysis are tedious, making software necessary to be used. The area of reinforcement required all the software provides that is similar, and the area reinforcement provided in detailing is also the same, which mean that all software is capable of analysis and design structure.  Keywords: Comparative study 1, Software 2, Analysi & Design